Influencing Factor Analysis of Break-bulk Cargo Freight Price Using SD Model - Mingbo Fan, Jiaxing Shi, Guanlin Li (Forest Chemicals Review, 2022)
Based on the influencing factors of shipping price of groceries, the system dynamics (SD) model is established and the corresponding flow chart is drawn. And according to the existing data of the same period, using the method of regression analysis to study the relationship between variables, according to the change of different variables and their mutual influence to analyze the change trend of grocery shipping price. The study found that due to the impact of COVID-19, the cost of fleet personnel, port operations and fuel costs have increased, leading to fluctuations in shipping prices of groceries. Relevant departments should actively pay attention to the situation of COVID-19, various costs of the fleet and the capacity of the world fleet in order to analyze the trend of shipping prices of groceries.